Assistance for Rice Farmers through Salibu Cultivation Technology to Create a Post-Pandemic Food Independent Village in Cijeler Sumedang Village - Riyanto Adji (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2022)
The increasing population in West Java has a major effect on the narrowing of land, this is natural because the land has turned into residential land. The narrowing of agricultural land cannot be resisted, but we must find alternative solutions, so that agricultural productivity can be maintained. One of the productivity of agricultural products that must be maintained is rice, because as the main source of rice, it becomes the staple food of the people of West Java. One of the steps to increase rice productivity is to use the SALIBU cultivation technology. The results of previous research regarding the SALIBU cultivation technology showed that rice productivity increased because of one planting and harvesting many times. The application of the SALIBU cultivation technology is not easy, therefore it is necessary to carry out the assistance socialization steps regarding the cultivation of the cruciferous, the aim is to get a response from the farmers, so that it can be used as a reference to the next stage of research. The method used is literature review, socialization and interviews. The results of the socialization stated that 44% of farmers wanted to learn the cruciferous cultivation technology, 40% of farmers answered that they were still unsure, and 16% said they did not know.